Analisis Keterampilan Teknik Servis Tenismeja Pada Ekstrakurikuler Di SMP Negeri 19 Palembang - Hikmah Lestari; Muhsana El Cintami Lanos; Puput Sekar Sari (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This study aims to determine the results and analyze table tennis service skills in students who take table tennis extracurricular at SMP Negeri 19 Palembang. This research is a quantitative descriptive research. The research sample was 15 students who took part in table tennis extracurricular activities. The results of this study are the forehand service skills of students with good classification as many as (3) people (20%), moderate classification (9) people (60%), poor classification as many as (3) people (20%). While the backhand service skills are very good classification students as many as (1) people (7%), good classification as many as (4) people (27%), moderate classification (8) people (53%), poor classification as many as (2) people ( 13%). Thus, it can be concluded that the results of the forehand and backhand service level of table tennis students who participate in table tennis extracurricular activities at SMP Negeri 19 Palembang can be categorized as moderate with an average forehand service of 5.5, while the average result of backhand serving is 4, 8.